2017
DOI: 10.1002/ejp.1136
|View full text |Cite
|
Sign up to set email alerts
|

Cortical nociceptive processes are reduced by visual alpha‐band entrainment in the human brain

Abstract: While it is known that visual stimulation can increase the brain's oscillatory alpha rhythms, here, we show that this increase in alpha power occurs alongside reduced cortical processing of nociception, as measured with EEG. This establishes an objective marker of alpha entrainment-based analgesia that may be useful in the development of neuromodulatory treatments for clinical pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 47 publications
(64 reference statements)
3
25
0
1
Order By: Relevance
“…The present study's findings build on the findings by Ecsy et al (Ecsy, Brown, and Jones 2018), who previously demonstrated that visual alpha stimulation can increase alpha power and reduce pain in an experimental pain setting. Ahn et al (2019) provided the first evidence that alpha stimulation can be used successfully in a clinical pain setting.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study's findings build on the findings by Ecsy et al (Ecsy, Brown, and Jones 2018), who previously demonstrated that visual alpha stimulation can increase alpha power and reduce pain in an experimental pain setting. Ahn et al (2019) provided the first evidence that alpha stimulation can be used successfully in a clinical pain setting.…”
Section: Discussionsupporting
confidence: 87%
“…However, where this study only included brief periods of stimulation, Ahn et al applied alpha tACS for 40 minutes. In an experimental pain setting with pain-free volunteers, Ecsy et al (2018; achieved a significant reduction in pain ratings using 10 minutes of auditory and visual stimulation and Arendsen et al (2018) applied alpha tACS for 15-20 minutes. This feasibility study focused primarily on the entrainment of alpha activity, where it has been shown that even very short periods of stimulation can entrain alpha oscillations (Herrmann 2001;Mathewson et al 2012;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the current findings invite more robust and comprehensive research on the role of EEG alpha rhythm during bodily threatening events. Such note of caution is particularly relevant in light of the recent suggestion to manipulate alpha oscillations through non-invasive brain stimulation (Arendsen, Hugh-Jones, & Lloyd, 2018;Hohn, May, & Ploner, 2019) or sensory entrainment (Ecsy, Brown, & Jones, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то, что имеется множество дополнительных методов обследования при данных заболеваниях: электромиография, вызванные потенциалы, МРТ, рентгенодиагностика и проч. диагноз в основном ставится путем скрупулёзного сбора анамнеза и клинической картины, что требует от врача времени и определенной подготовленности в диагностике данных заболеваний [1,2].…”
unclassified